2007
DOI: 10.1111/j.1399-5448.2006.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1*08 allele may help to distinguish between type 1 diabetes mellitus and type 2 diabetes mellitus in Mexican children

Abstract: There are significant differences in the HLA profile in Mexican children with T1DM and T2DM. HLA typing could play a role in the differentiation between both types of diabetes in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
(65 reference statements)
2
5
0
1
Order By: Relevance
“…[18,24,25] A study with type 1 diabetes reported low frequency for DRB1*04 and DRB1*08 whereas in other studies with rheumatoid arthritis and systemic lupus erythematosus, the frequency for DRB1*08 was significantly high. [26][27][28][29] In the present study in concordance with the previous studies, the frequency of HLA-DRB1*03 was significantly high in the patient group suggesting that this allele might be associated with disease susceptibility. On the other hand, the high frequency of HLA-DRB1*13 and DRB1*08 alleles in the control group and the lower frequency in the patient group indicates a protective role for this allele also in Turkish population.…”
Section: Discussionsupporting
confidence: 92%
“…[18,24,25] A study with type 1 diabetes reported low frequency for DRB1*04 and DRB1*08 whereas in other studies with rheumatoid arthritis and systemic lupus erythematosus, the frequency for DRB1*08 was significantly high. [26][27][28][29] In the present study in concordance with the previous studies, the frequency of HLA-DRB1*03 was significantly high in the patient group suggesting that this allele might be associated with disease susceptibility. On the other hand, the high frequency of HLA-DRB1*13 and DRB1*08 alleles in the control group and the lower frequency in the patient group indicates a protective role for this allele also in Turkish population.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of T1DM is rapidly increasing in specific regions and shows a trend toward earlier age of onset and also it is highly variable among different ethnic groups (6,7,8,9,10,11,12,13,14,15). It is predicted that the overall incidence of T1DM is about 40% higher in recent years as compared to its incidence in 1997 (16).…”
Section: Discussionmentioning
confidence: 99%
“…T1DM is an autoimmune disorder and the risk for the disease is increased by specific HLA DR/DQ alleles [e.g., DRB1*03-DQB1*0201 (DR3) or DRB1*04-DQB1*0302 (DR4)] (2,3,4,5). Trends in the frequency of HLA DR-DQ haplotypes showed different associations in distinct ethnic groups (6,7,8,9,10,11,12,13,14,15) and also in the same region (11). With these variations in mind, T1DM patients and healthy controls from the population of the Southeast Region of Turkey were investigated for HLA DR-DQ haplotypes.…”
Section: Introductionmentioning
confidence: 97%
“…In their article published in this issue of Pediatric Diabetes (pp. 5–10), Julio Granados and his group suggest using human leukocyte antigen (HLA) class II typing to better distinguish between the two syndromes based on the observation that the frequency of HLA‐DRB1*08 alleles was found increased in children with T2D when compared with patients with T1D (3).…”
mentioning
confidence: 99%
“…The question then remains whether the DRB1*08 allele actually is – as suggested by Granados and colleagues (3)– a marker of T2D or just the most frequent allele in a population, like the Mexican children, once the carriers of the best T1D markers (e.g. DQ2 and DQ8) are excluded and, thus, the DRB1*03 and *04 alleles are not considered in the comparison.…”
mentioning
confidence: 99%